2017
DOI: 10.1159/000455229
|View full text |Cite
|
Sign up to set email alerts
|

MRI of Cerebellar Infarction

Abstract: Background: MRI is the imaging modality of choice for diagnosing brain infarction. Because of few or atypical clinical symptoms and a relatively low sensitivity of CT scans, many cerebellar infarctions may be detected only with MRI. With adequate recognition of cerebellar infarction on MRI and prompt initiation or optimisation of preventive therapeutic measures, more dramatic strokes may be avoided in selected cases. Summary: We first briefly review the clinical presentation of cerebellar infarctions, followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 41 publications
0
31
0
Order By: Relevance
“…In recent studies analyzing small, asymptomatic, chronic CI (resembling what we called SCCI in our study), association with markers of atherothrombotic cerebrovascular disease was observed suggesting artery-to-artery embolic origin of these cerebellar cortical cavities [11–16]. However, in these studies no details were given on the proportion of patients having had ≥24 h ECG monitoring (to detect the most frequent cause of cardioembolism, i.e.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…In recent studies analyzing small, asymptomatic, chronic CI (resembling what we called SCCI in our study), association with markers of atherothrombotic cerebrovascular disease was observed suggesting artery-to-artery embolic origin of these cerebellar cortical cavities [11–16]. However, in these studies no details were given on the proportion of patients having had ≥24 h ECG monitoring (to detect the most frequent cause of cardioembolism, i.e.…”
Section: Discussionmentioning
confidence: 73%
“…Another study showed cortical cerebellar microinfarctions in one third of patients with recent symptomatic vertebral artery stenosis [12]. These data suggest that these cortical cerebellar cavities are related to artery-to-artery embolism [11–16].…”
Section: Introductionmentioning
confidence: 97%
“…Anatomical variations are most commonly seen as caudal AICA atresia or rostral duplicate AICA occlusion (Chen, Chen, Diaz‐Marchan, Schomer, & Kumar, 2018). Moreover, the territory perfused by the AICA may overlap with that of the marginal branch of the superior cerebellar artery (SCA); thus, the MCPs could be supplied by the SCA directly or by a watershed zone supplied by both vascular territories in patients with an AICA variation (De Cocker, Lövblad, & Hendrikse, 2017; Kataoka, Izumi, & Kinoshita, 2011; Rhoton, 2000). Moreover, some studies reported that bilateral MCP infarctions could be attributed to varying degrees of vertebral artery occlusion or stenosis (De Cocker et al., 2017; John, Hegazy, Cheng Ching, & Katzan, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Symmetrical hyperintensity of both MCPs on T2-weighted imaging (f) suggests Wallerian degeneration of the pontocerebellar fibersSchomer, & Kumar, 2018). Moreover, the territory perfused by the AICA may overlap with that of the marginal branch of the superior cerebellar artery (SCA); thus, the MCPs could be supplied by the SCA directly or by a watershed zone supplied by both vascular territories in patients with an AICA variation (De Cocker, Lövblad, & Hendrikse, 2017;Kataoka, Izumi, & Kinoshita, 2011;Rhoton, 2000).Moreover, some studies reported that bilateral MCP infarctions could be attributed to varying degrees of vertebral artery occlusion or stenosis(De Cocker et al, 2017;John, Hegazy, Cheng Ching, & Katzan, 2013). Therefore, alterations in the vertebrobasilar system, especially the AICA, should be considered as a possible cause of isolated bilateral MCP infarctions.…”
mentioning
confidence: 99%
“…The inclusion criteria were as follows: patients diagnosed with cerebral infarction based on transcranial magnetic resonance imaging or computed tomography scan findings [12], those with stable vital signs who were admitted to the hospital within 48 h after the onset of cerebral infarction, those with detailed general clinical data and expected survival time ≥3 months, and those with firstepisode cerebral infarction or recurrent cerebral infarction that did not cause any neurologic impairment. This study was approved by the Ethics Committee of the Second Hospital of Hebei Medical University.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%